Migrant and refugee students from the Global South at Austrian universities: A typology for targeted support - Judith Kohlenberger; Theresa Herzog; Tobias Schnitzler (Austrian Foundation for Development Research (ÖFSE), 2022)
Drawing on qualitative data from five focus group discussions (N=23), we developed a typology with migrant and refugee students from the Global South living in Vienna and studying at an Austrian university. Our findings indicate that different levels of support are required, depending on both structural and personal factors that respondents displayed. Structural factors include residence permit, field and level of study and conditions at the university (such as digital access, student representation, supervision by professors, workload). Personal factors involve respondents' social capital in terms of social network and friends/colleagues, in particular in the form of in/formal mentoring, language skills and other qualifications, personal resilience and aspirations, and mental health. Based on these factors, our typology differentiates between four different types of migrant and refugee students from the Global South, who differ with regard to the quality of their experience at university and their general well-being, which in turn impacts their study success.
Keywords: 330; refugees; higher education; Global South; development; university; inclusion; typology; Austria